Structural carbon/epoxy prepregs properties comparison by thermal and rheological analyses - Costa, Michelle Leali; Rezende, Mirabel Cerqueira; Faulstich de Paiva, Jane Maria; Botelho, Edson Cocchieri (Taylor & Francis Inc, 2006)
Two different carbon/epoxy prepreg materials were characterized and compared using thermal (DSC, TGA, and DMA) and rheological analyses. A prepreg system (carbon fiber preimpregnated with epoxy resin F584) that is currently used in the commercial airplane industry was compared with a prepreg system that is a prospective candidate for the same applications (carbon fiber prepreg/epoxy resin 8552). The differences in the curing kinetics mechanisms of both prepreg systems were identified through the DSC, TGA, DMA, and rheological analyses. Based on these thermal analysis techniques, it was verified that the curing of both epoxy resin systems follow a cure kinetic of n order. Even though their reaction heats were found to be slightly different, the kinetics of these systems were nevertheless very similar. The activation energies for both prepreg systems were determined by DSC analysis, using Arrhenius's method, and were found to be quite similar. DMA measurements of the cured prepregs demonstrated that they exhibited similar degrees of cure and different glass transition temperatures. Furthermore, the use of the rheological analysis revealed small differences in the gel temperatures of the two prepreg systems that were examined.
Keywords: cure behavior; cure kinetics; prepreg; rheological properties; thermal analysis